2012
DOI: 10.1177/2046147x12448580
|View full text |Cite
|
Sign up to set email alerts
|

Transparency matters: The concept of organizational transparency in the academic discourse

Abstract: Although transparency is currently a buzzword in the public discourse, public relations (PR) theory has not yet produced a theory of transparency. Instead, its body of knowledge lacks theoretical depth and critical perspectives. Taking this as a point of departure, the article searches for alternative accounts on transparency, which could stimulate PR discourse and help to overcome the theoretical and normative deficits. Therefore it aims to discern whether or not the discourse in related disciplines such as b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 96 publications
(95 reference statements)
1
62
0
1
Order By: Relevance
“…Transparency is a way to achieve accountability and public trust in organizations [26,29,32,33]. It is a roadmap to enhance financial and organizational performance [34], and to drive the effectiveness of the company and extend democratic practice [35]. As an antecedent, transparency impacts positively on public trust.…”
Section: Transparency and Effective Humanitarian Logistics (Hl)mentioning
confidence: 99%
“…Transparency is a way to achieve accountability and public trust in organizations [26,29,32,33]. It is a roadmap to enhance financial and organizational performance [34], and to drive the effectiveness of the company and extend democratic practice [35]. As an antecedent, transparency impacts positively on public trust.…”
Section: Transparency and Effective Humanitarian Logistics (Hl)mentioning
confidence: 99%
“…At RU, the questions of "what to share" and "whom to share it with" looms large. I noted earlier that the literature reports relatively few objections to being transparent (see Wehmeier and Raaz, 2012). At the same time-being transparent, especially fully transparent-does have implications.…”
Section: Chart 3: Example Of Phd Program X Faculty Counts Summary Chamentioning
confidence: 99%
“…Insights from the Literature Numerous studies have been completed on the topic of organizational transparency. There have been recent studies that have identified the advantages and risks associated with being transparent (e.g., Bennis, Goleman, and O'Toole, 2008); different types of transparency (e.g., Nicolaou, 2010); a framework for identifying positive frames or categories of transparency (e.g., Wehmeier and Raaz, 2012), and even some publications that have suggested principles of transparency (Noveck, 2013).…”
Section: Different Types Of Transparencymentioning
confidence: 99%
See 1 more Smart Citation
“…Albu and Flyverbom (, 5) review the transparency literature relating to the study of organizations and conclude that “in most accounts, transparency is associated with the sharing of information” about an organization's processes, procedures, functioning, and performance. Zooming in, we find studies that measure “transparency as [the] frequency of information disclosure” (Berglund , 360; emphasis added), relate the existence of transparency to the accuracy of disclosed information (Wehmeier and Raaz ), or agree that disclosed information has to be relevant for interested parties in order to create transparency (Rawlins ).…”
Section: Theoretical Contextmentioning
confidence: 99%